Bioresorbable scaffold — A magic bullet for the treatment of coronary artery disease?. (15th July 2016) - Brie, Daniel; Penson, Peter; Serban, Maria-Corina; Toth, Peter P.; Simonton, Charles; Serruys, Patrick W.; Banach, Maciej
Abstract: Today, drug-eluting metal stents are considered the gold standard for interventional treatment of coronary artery disease. While providing inhibition of neointimal hyperplasia, drug-eluting metal stents have many limitations such as the risk of late and very late stent thrombosis, restriction of vascular vasomotion and chronic local inflammatory reaction due to permanent implantation of a 'metallic cage', recognized as a foreign body. Bioresorbable scaffold stents (BRS) are a new solution, which is trying to overcome the limitation of the 'metallic cage'. This structure provides short-term scaffolding of the vessel and then disappears, leaving nothing behind. The purpose of this review is to present the theoretical rationale for the use of BRS and to outline the clinical outcomes associated with their use in terms of data obtained from RCTs, clinical trials, registries and real life use. We have also tried to answer all questions on this intervention based on available data, with a focus on ABSORB BVS (Abbott Vascular, Santa Clara, USA). We consider that this new technology can be the " magic bullet " to treat coronary artery disease. Highlights: Today, drug-eluting metal stents are considered the gold standard for CAD interventional treatment. The ABSORB IV trial will help to explain the concerns associated with the BRS thrombosis and risk of any-cause MI/TVMI. BRS are a new solution, which can be the " magic bullet " to treat coronary artery disease.